Analisis Dana Zakat, Penerimaan Non Halal, dan Corporate Social Responsibility (CSR) Pada Bank Syariah Di Indonesia - Syafina, Laylan; Nurwani, Nurwani (Universitas Alma Ata, 2021)
Zakat funds are funds obtained from Muslim assets that have exceeded the haul and nisab that must be fulfilled. Zakat funds have the opportunity to improve the people's economy. Zakat funds are also related to non-halal receipts which are reflected in reports on the sources and uses of benevolent funds. This report is usually related to social activities, which means it is related to the CSR of the Islamic bank. The study was conducted on all Islamic commercial banks in Indonesia starting from 2016 to 2020. Using eviews 7 to analyze the data. The results of this study show that zakat funds and non-halal revenues partially and significantly influence Corporate Social Responsibility (CSR) and simultaneously zakat funds and non-halal revenues also have a significant and significant effect on Corporate Social Responsibility (CSR).